Severe hypoxia related to uncomplicated atrial septal defect. - Siderys, H (1993)
A 73-year-old man was admitted to our institution with severe hypoxia. Cardiac catheterization and transesophageal echocardiography revealed an atrial septal defect with an interatrial right-to-left shunt but with no pulmonary hypertension. Direct examination at surgery revealed an elongated thoracic aorta that caused the aortic annulus to reside at the level of the diaphragm and the heart to be positioned transversely in the mediastinum. Surgical closure of the atrial septal defect normalized oxygenation. We attribute the unusual occurrence of an atrial septal defect and a right-to-left shunt in the absence of pulmonary hypertension to the spatial and mechanical changes caused by the patient's elongated aorta and by the transverse position of the heart.